The epidemiology of injuries at the London 2012 Paralympic Games - Willick, S. E.; Webborn, N.; Emery, C.; Blauwet, C. A.; Pit-Grosheide, P.; Stomphorst, J.; Van de Vliet, P.; Patino Marques, N. A.; Martinez-Ferrer, J. O.; Jordaan, E.; Derman, W.; Schwellnus, M. (British Journal of Sports Medicine, 2013)
Background The characteristics and incidence of injuries at the Summer Paralympic Games have not previously been reported. A better understanding of injuries improves the medical care of athletes and informs future injury prevention strategies.Objective The objective of this prospective cohort study was to characterise the incidence and nature of injuries during the London 2012 Summer Paralympic Games.Methods Injury information was obtained from two databases. One database was populated from medical encounter forms completed by providers at the time of assessment in one of the medical stations operated by the Organising Committee. The second database was populated daily with information provided by team medical personnel who completed a comprehensive, web-based injury survey.Results The overall injury incidence rate was 12.7 injuries/1000 athlete-days. Injury rates were similar in male and female athletes. The precompetition injury rates in women were higher than those in the competition period. Higher injury rates were found in older athletes and certain sports such as football 5-a-side (22.4 injuries/1000 athlete-days). Overall, 51.5% of injuries were new onset acute traumatic injuries. The most commonly injured region (percentage of all injuries) was the shoulder (17.7%), followed by the wrist/hand (11.4%), elbow (8.8%) and knee (7.9%).Conclusions This is the largest and most comprehensive epidemiological report examining injuries in Paralympic athletes. Injury rates differ according to age and sport. Upper limb injuries are common. The knowledge gained from this study will inform future injury surveillance studies and the development of prevention strategies in Paralympic sport. The Epidemiology of Injuries at the London 2012 Paralympic Games.